LANGUAGE LEARNING DIFFICULTIES OF A DEAF STUDENT AT SMA LUAR BIASA PUTRA JAYA MALANG - FAJRINA, NUR (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Second Language Learning (SLL), Learning Difficulties, Causes of Learning Difficulties, Deaf Student.There are two kinds of language, verbal and non-verbal. Although verbal language is mostly used, there are people who cannot produce it properly. Deaf is one of reasons for this inability. The causes of deaf range from inborn to severe illness. The language used by deaf people is called sign language. In their learning process, deaf students experience several difficulties due to their disability. This research aims to discover the difficulties experienced by the deaf students. In this research, deaf student is chosen as the object. There are two research problems investigated namely;(1) What are the difficulties experienced by a deaf student of SMA Luar Biasa Putra Jaya in learning English? (2) What are the causes of learning difficulties experienced by a deaf student of SMA Luar Biasa Putra Jaya in learning English?The method that is used in this research is observation because it is a case study with qualitative approach. The data sources of this research are Budi’s responses to the teacher during learning English class and the result of interview with the teacher about Budi’s behaviour and also his causes of the difficulties in learning.The result of this research shows that there are nine characteristics in learning difficulty found in Budi. Those difficulties are memory difficulties, organisational difficulties, writing difficulties, visual processing difficulties, reading difficulties, auditory processing difficulties, time management difficulties, sensory difficulties, and sensory overload. Meanwhile, there are ten causes in learning difficulty, those are; classroom environment, socio-economic disadvantage, poor school attendance, health problem, learning through the medium of a second language, loss of confidance, emotional or behavioral problems, below average intellegence, sensory impairment, and specific information processing difficulties. In short, Budi experiences some difficulties that prevent him from learning English optimally. Thus, there should be some treatments aiming to guide Budi towards his success in learning English.The researcher suggests the next researchers, who want to conduct further research on this topic, use other theories or other aspects in learning difficulties not only to deaf student, but maybe to autism students.